Thermal radiation impact on MHD heat transfer natural convective nano fluid flow over an impulsively started vertical plate - Kumar, M. Anil; Reddy, Y. Dharmendar; Rao, V. Srinivasa; Goud, B. Shankar (Case studies in thermal engineering, 2021)
A numerical model is employed for the nanofluid flow and heat transfer from an infinite vertical plate in the existence of a magnetic field, thermal radiation and viscous dissipation. The solution of the basic governing equations was obtained by the finite element procedure. A collection of nanofluids with a fraction of nanoparticle volume comprising nanoparticles of aluminium oxide, copper, and titanium oxide is included less than or equal to 0.04. With the aid of non-dimensional flow parameters, the mathematical results of velocity and temperature distributions are analysed and shown diagrammatically. It is found that velocity and Temperature profiles enhance by enhancing the value of radiation parameter. The current simulations outlined are relevant for the processing of magnetic nanomaterials in the chemical industry and the metallurgy sector.